แนวทางการประชาสัมพันธ์ข้อมูลข่าวสารของเทศบาลตำบลโพนทอง อำเภอโพนทอง จังหวัดร้อยเอ็ด - คงสมกัน, พรพรรณ (วารสารศรีล้านช้างปริทรรศน์; Vol 2 No 2 (2016): วารสารศรีล้านช้างปริทรรศน์ ปีที่ 2 ฉบับที่ 2 (กรกฏาคม - ธันวาคม 2559), 2016)
บทความเรื่องนี้ มีวัตถุประสงค์เพื่อ 1.เพื่อศึกษา สภาพปัญหาและอุปสรรค ของการประชาสัมพันธ์เทศบาลตำบลโพนทอง อำเภอโพนทอง จังหวัดร้อยเอ็ด และ 2. เพื่อศึกษาแนวทางการประชาสัมพันธ์เทศบาลตำบลโพนทอง อำเภอโพนทอง จังหวัดร้อยเอ็ด โดยใช้แบบสัมภาษณ์เชิงลึก (In-depth Interview) กับ คณะผู้บริหารเทศบาล จำนวน 11 คน และใช้แบบสอบถาม (Questionnaires) กับประชาชนในชุมชน จำนวน 360 คน ด้วยการวิเคราะห์ข้อมูลและการแจกแจงความถี่ และร้อยละ ผลการศึกษา พบว่าระบบการประชาสัมพันธ์ของเทศบาลตำบลโพนทองมีข้อบกพร่อง ได้แก่ การเผยแพร่ข่าวสารล่าช้าและไม่สอดคล้องกับรายละเอียดกิจกรรมที่จัดขึ้น เทศบาลไม่มีการกำหนดนโยบายหรือวางแผนการประชาสัมพันธ์กิจกรรม งบประมาณและบุคลากรด้านการประชาสัมพันธ์มีไม่เพียงพอในการบริหารงาน ข้อมูลข่าวสารที่เผยแพร่ไปบางส่วนไม่ตรงกับความต้องการของประชาชน สื่อต่าง ๆ ที่เทศบาลนำมาใช้ในการประชาสัมพันธ์ไม่มีประสิทธิภาพและประสิทธิผล สำหรับการพัฒนากลยุทธ์การประชาสัมพันธ์เทศบาลตำบลโพนทอง มีแนวทางในการพัฒนาดังนี้ 1) ด้านการวางแผนการปฏิบัติงาน ในการปฏิบัติงานควรมีการวางแผนก่อนการดำเนินการ และจัดลำดับความสำคัญ 2) การพัฒนาการบริหารจัดการข้อมูลข่าวสาร การให้ข้อมูลข่าวสารในกิจกรรมต่าง ๆ ต้องมีความแม่นยำ ถูกต้องและเป็นไปตามโครงการที่ได้แจ้งไว้ 3) ด้านบุคลากรผู้ปฏิบัติงาน ควรเพิ่มบุคลากร หรือสร้างเครือข่ายเพิ่ม เช่น ให้ผู้บริหาร หรือชุมชนเข้ามามีส่วนร่วมในการให้ข้อมูลข่าวสาร 4) การใช้สื่อเพื่อให้เข้าถึงประชาชน เทศบาลควรปรับปรุงให้มีประสิทธิภาพและประสิทธิผลมากยิ่งขึ้น 5) ด้านงบประมาณ ควรเพิ่มเติมงบประมาณด้านการประชาสัมพันธ์ให้เพียงพอแก่การปฏิบัติงาน           This paper has the objectives on 1. a study of problems, obstacle, examine the perception of information of inhabitants of Phonthong Sub-District Municipality and 2 Guidances of Information Province of Phonthong Sub-District Municipality, Phonthong District, Roi - Ed Province, through an in-depth interview of 11 municipality administrators. Questionnaires were used to inquire 380 inhabitants through content analysis, frequency, and percentage. The research results are that the public relations system of Phonthong Sub-District Municipality has some problems and deficiencies such as information dissemination is too slow and not co-incident with the details of activities. The municipality has not a clear policy implementation or plan of public relations activities. The lack of budgeting as well as staff and personnel on public relations is not inadequately sufficient. Some information distributed is not directly to the residents’ need. The medias the municipality has applied in the area are inefficiency and ineffective. The tactics on public relations development of Phonthong Sub-District Municipality are following. 1) Operational Planning: Before starting projects the municipality should have action plan and make priority. 2) Development of information management: Disseminations of information on the projects should be accurate and infallible. 3) Staffing: Public relation staffs should be affixed or contribute a public relation network like administrators and communities could join the line to provide information. 4) The use of medias to access to the People: The medias of Phonthong Sub-District municipality should be improved to be more efficiency and effectiveness. 5) Budgeting: The public relation budget should be increased as to sufficient enough for the operation.